Enhancing Aqidah Akhlak Learning Outcomes through Student Teams Achievement Division (STAD) - Ishak Ishak; Shoviyul Himami; Ahsanatul Khulailiyah; Desy Naelasari; Mei Dwi Ariskiyah (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2026)
This study examined the effectiveness of the Student Teams Achievement Division (STAD) cooperative learning model in improving students’ Aqidah Akhlak learning outcomes at MTs Sunan Gunung Jati Kabuh Jombang. The study was motivated by the need for student-centered instructional approaches capable of enhancing learning achievement and classroom engagement in Islamic Religious Education. A quantitative approach employing a quasi-experimental design was used. The participants consisted of 30 eighth-grade students divided into an experimental group and a control group. Data were collected through achievement tests, while validity, reliability, normality, homogeneity, and hypothesis testing were conducted to ensure data quality and statistical accuracy. The findings revealed that the research instrument was valid and reliable, with a Cronbach’s Alpha coefficient of 0.869. The results of the normality and homogeneity tests indicated that the data met the assumptions required for parametric analysis. Descriptive statistics showed that the experimental group achieved a higher mean score (M = 75.33) than the control group (M = 62.60). Furthermore, the t-test analysis produced a significance value of 0.002 (p < 0.05), indicating a statistically significant difference between the two groups. These findings demonstrate that the implementation of the STAD cooperative learning model significantly improved students’ Aqidah Akhlak learning outcomes. The study contributes to the growing body of literature on cooperative learning in Islamic education and highlights the potential of student-centered instructional strategies to enhance academic achievement and learning engagement. The findings also provide practical implications for teachers seeking more interactive and effective approaches to Aqidah Akhlak instruction